Memahami Narasi Perempuan yang Menikah Usia Dini - Ika Putri Hanafi; Hapsari Dwiningtyas Sulistyani; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Early marriage is one form of marginalization in which women have to go through various forms of communication dominance in the process of making the decision to get married. This brings many problems in the decision-making process within the household. Therefore, the aim of this research is to understand how the communication process of decision-making occurs, both before deciding to get married and during the marriage itself. Three interviewees with different marriage backgrounds will be interviewed to observe how the communication process in decision-making unfolds. The research will be conducted using Labov's narrative analysis method.The results of this study indicate that women's early marriage decisions are caused by manipulation in the form of continuous pressure to get married and threats of ending the relationship, which can change their minds. Manipulative actions also result in women willingly altering the narrative about men in front of their parents to gain their approval. After marriage, it was found that women's involvement in household decision-making is limited due to manipulation by husbands through narratives of masculinity. Furthermore, women's early marriage decisions are influenced by feelings of guilt for violating societal norms, such as unwanted pregnancies. As a result, the improper position leads to double marginalization and a lack of involvement in household decision-making after marriage. Another factor contributing to women's early marriage decisions is fulfilling their parents' wishes by entering arranged marriages, where the interests of the parents appear more important. However, after marriage, women can fully participate in household decision-making, including financial decisions, parenting styles, and reproduction, as the positions of husband and wife are equal, and there is no fixed division of roles for either spouse.